Network Maketing: Analisis Terhadap Pemasaran Jejaring Dalam Penjualan Langsung Berjenjang Syariah - Rohimin Rohimin (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2016)
This paper describing the dynamics and development of the marketing system in the tiered direct network sales in Sharia. The main idea of this paper seeks to examine the rules set out in DSN-MUI Fatwa No. 75 on Tiered Direct Networking Sales, will be observed also on the system of Multi Level Marketing (MLM). Both forms of patterns, methods, and this sales system in practice can be justified and considered in accordance with sharia and do not harm the public or causing things that are forbidden when the object of the transaction clearly a product or service, not something that is forbidden or used for something forbidden and it must not contain gharar, gambling, usury, dharar, dzulm, and immorality. Another instrument to note also is the problem of excessive mark-ups (rising prices or excessive cost, granting commissions or bonuses passive and cause ighra ‘(appeal overload). Application of marketing in tiered direct network sale can not be easily termed as sharia if it just hold and guided by the DSN-MUI Fatwa No. 75 / DSNMUI / VII / 2007, but needs to be adapted to the MUI Fatwa DSN other related and a Decree of the Minister of Industry and Trade related issues. Marketing Network in tiered direct network sale and multi Level marketing including marketing practices that could be waged with dynamic multi aqad accordance with the contract required and agreed.